Analisis Fatwa DSN MUI Dalam Transaksi Pembiayaan Murābaḥah Di KSPP. Syariah BMT NU Cabang Pragaan - Umam, Khairul; Supriyadi (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2025)
This study aims to find out how the implementation of murābaḥah financing based on fatwa DSN MUI no. 04/DSN-MUI/IV/2000 at KSPP Syariah BMT NU Pragaan Branch. This research method uses field qualitative, with data collection by observation, interviews, and documentation. The results showed that the general provisions of murābaḥah financing to the type of guarantee used in the Sharia KSPP BMT NU Pragaan Branch were in accordance with the fatwa of DSN MUI no. 04/DSN-MUI/IV/2000. Where in its application, if there are doubtful things related to murābaḥah financing transactions, the Sharia KSPP Center BMT NU East Java held a bahtsul masail by presenting the chairman of the Indonesian Ulema Council (MUI) East Java. As for the purchase of goods at KSPP Syariah BMT NU Pragaan Branch using two options, the first purchase of goods is carried out by the manager himself and the second is purchased by partners as representatives of the manager.